Influence of freestall building orientation on comfort of lactating dairy cattle during summer heat stress - John F. Smith; Joseph P. Harner; Michael J. Brouk (Kansas Agricultural Experiment Station Research Reports, 2001)
A trial was conducted during the summer of 2000 to evaluate the effect of freestall building orientation"”east-west vs. northsouth"” on respiration rates of lactating dairy cows, temperature-humidity index (THI) in the barns, barn temperature, and barn humidity. Differences between ambient and barn temperature and THI were higher in east-west vs. north-south orientated barns. Respiration rates were higher in north-south than in east-west orientated structures. The magnitude of differences between barn and ambient temperatures and THI did not fully explain differences in respiration rates between north-south and east-west orientated barns. Other factors such as solar radiation, airflow, and animal stress may have contributed to the differences in respiration rates.; Dairy Day, 2001, Kansas State University, Manhattan, KS, 2001;
Keywords: Dairy Day; 2001; Kansas Agricultural Experiment Station contribution; no. 02-133-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 881; Dairy; Heat stress; Freestalls; Cow comfort